THE TREATMENT OF NEOVASCULAR GLAUCOMA CAUSED BY CENTRAL VEIN OCCLUSION WITH CYCLOCRYOTHERAPY-A CASE REPORT - Rushiti, Muhamedin; Bogdanova, Irina (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Glaucoma is the world's number one cause of irreversible blindness. Worldwide, there are over 65 million people diagnosed with various types of glaucoma. According to the latest definitions, it is a neuropathic progressive disease of the optic nerve. The main divisions are primary open and closed angle glaucoma and secondary glaucoma which is caused by various systemic or local diseases. Among the most common types of secondary glaucoma is neovascular glaucoma, which can be caused by diabetic retinopathy, arterial hypertension, various vasculopathies, inflammatory processes of the eye, trauma and other factors. Neovascular glaucoma is a serious and aggressive form of glaucoma that has rapid progression and manifestations. The main symptoms are high eye pressure, pain, redness and the appearance of small vessels in the iris.There are various treatments for this disease, but mainly they are aimed at relieving the symptoms or reducing the progression of the disease. The most important therapeutic options, apart from anti-glaucoma drugs, are the application of anti-Vegf therapy and cyclodestructive treatments, which enable the reduction of intraocular pressure and alleviation of symptoms, thus enabling patients to have a better quality of life.The aim of our study was to prove the impact of cyclocryotherapy in reducing intraocular pressure in a 43-year-old female patient. age with neovascular glaucoma of the left eye. The pressure before the intervention was 41.4 mmHg, while after the intervention it decreased to 26.6 mmHg, also the symptoms such as pain and redness subsided. Key words; Neovascular glaucoma, retinal vein occlusion, cyclo-cryotherapy.